A Curriculum for Ultrasound-Enhanced Physical Examination Rounds - David Frost; Maral Nadjafi; Rodrigo Cavalcanti (Association of American Medical Colleges, 2013)
Abstract Introduction This is a curriculum for teaching evidence-based bedside physical examination rounds augmented by bedside point-of-care ultrasound. This resource includes all of the information necessary to present the curriculum, including relevant evidence for physical maneuvers and detailed instructions on how to demonstrate findings by examination and with ultrasound. Methods The main resource file is a manual to guide clinician teachers with step-by-step instructions and detailed explanations to allow them to conduct bedside sessions whereby physical examination teaching is combined with ultrasound. We have selected eight clinical scenarios particularly given to this combined approach. Topics covered include splenomegaly, ascites, pleural effusion, mitral regurgitation, tricuspid regurgitation, pulmonary hypertension, left-ventricular systolic dysfunction, volume assessment, and examination of the neck vessels. Results We have evaluated trainee perception of this curriculum's usefulness after a year of implementation. Residents felt that it enhanced physical examination teaching, made them more comfortable with bedside ultrasound, and made them more comfortable performing bedside procedures. We are in the process of objectively assessing competence in performing point of care ultrasound in our trainees. Discussion This resource represents, to our knowledge, the first comprehensive curriculum that combines evidence-based physical diagnosis teaching with point-of-care ultrasound. We have specifically chosen clinical scenarios that are well suited to this hybrid methodology.